The Effect of Anticipation Guide Strategy on Students' Reading Comprehension of Explanation Text - Dewi Damayanti (National Conference on Language, Education, and Technology Proceeding, 2023)
The objectives of this research are to know : 1. The application of anticipation guide strategy on students reading comprehension of explanation text, 2. The students reading comprehension of explanation text before and after using anticipation guide strategy 3. Is there any significant effect of anticipation guide strategy on students reading comprehension of explanation text at the eleventh grade of SMK Negeri 1 Tantom Angkola. This research use experiental method with one group pre-test and post-test design. The population are 175 with 36 sample take by purposive sampling. The instruments of this research are observation sheet and test form multiple choices. The application of anticipation guide strategy get score 3.76 which categorized very good. Students mean score in pretest is 51.4 and 75.44 in post test. The data is analyze by using t test formula. The result of data analyzing t test is higher than t table (22.64>2.03). The hypothesis is accepted, it means that there is any significant effect of anticipation guide strategy on students reading comprehension of explanation text at the eleventh grade of SMK Negeri 1 Tantom Angkola in 2022/2023 Academic Year. Keyword: Anticipation Guide, Strategy, reading, comprehension, Explanation Text